Korporativno upravljanje javnih zavodov v Republiki Sloveniji - Bohinc, Rado (Podjetje in delo, 2020)
Corporate governance law of public-law entities includes rules that determine the position of the founder, the relationship between the founder and the management bodies, the powers, responsibilities and interrelationships of the bodies of public entities, taking into account principles such as transparency, separation of management and supervision, balance between powers and responsibilities and integrity, risk management and control mechanisms; all in a way that achieves the purpose of providing public services, that is, the efficient and accessible fulfilment of public needs. Better corporate governance of public-law entities contributes to more efficient use of public funds, cost reduction, the elimination of corruption, and increased performance in the provision of public services. The purpose of this paper is to show some of the weaknesses of the current legal rules and consequently the bad corporate governance practices of public-law entities, and to substantiate some de lege ferenda proposals. We focus mainly on issues such as the classification of public institutions according to various criteria; we substantiate the necessity of delimiting the status and legal delimitation of public institutions into those that carry out market activities from those that perform non-market activities, following the example of EU law. The article substantiates the criticism on non-consistent delimitation of competences and responsibilities between the founder, the council and the director of the public institution; the proposal for the implementation of a one- and two-tier management system of public institutions is explained. The article also analyses the strengths and weaknesses of the use of corporate governance models from the private corporate sector for public-law entities and evaluates the ways of direct applicability. The research methodology in this paper is based on the analysis of domestic and foreign legislation and literature in this field, on the comparative method with the analysis of advantages and disadvantages of corporate governance in the private sector, and evaluation of the applicability of the private model in the public sector.